EFEKTIVITAS MODEL PEMBELAJARAN EXPLICIT INSTRUCTION (PENGAJARAN LANGSUNG) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DISMKS PANCADHARMA PADANGSIDIMPUAN - Try Hayati Siregar (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2019)
ABSTRACT The aim of this study is to describe of using explicit instruction model on students’ mathematical communication ability on the topic of statistics at the eleventh grade students of SMKS Pancadharma Padangsidimpuan. This research was conducted by applying experimental (one group pre test post test design) with 30 students as the sample and they were taken by using cluster sampling technique from 59 students. Observation and test were used in collecting the data. Based on descriptive analysis, it was found: (a) the average of using explicit instruction model was 3.40 (very good category) and (b) the average of students’ mathematical communication ability on the topic of statistics before using explicit instruction model was 58.90 (fair category) and after using explicit instruction model was 82.10 (very good category). Furthermore, by using pair sample ttest (SPSS V22) and N-Gain, the result showed the significant value was less than 0.05 (0.000<0.05) and g= 0.64 (middle category). It means, explicit instruction model was effective used on students’ mathematical communication ability on the topic of statistics at the eleventh grade students of SMKS Pancadharma Padangsidimpuan. Keywords: explicit instruction model, mathematical communication ability